Longipone A, a unique tricyclic polyketide from the fungus Xylaria longipes. (8th June 2021) - Li, Jing; Li, Lan-Qing; Tan, Gui-Shan; Liu, Shao; Wang, Wen-Xuan; Liu, Ji-Kai
Graphical abstract: Highlights: A novel polyketide was identified from the fungus Xylaria longipes. The structure was determined by 1D/2D NMR and single crystal X-ray diffraction. It showed moderate cytotoxicity against human cancer cell lines. Abstract: Longipone A (1 ), a novel polyketide containing a tetrahydro-anthracene core structure, was isolated from the liquid fermentation of fungus Xylaria longipes . Its structure, including absolute configuration, was determined on the basis of spectroscopic data and X-ray crystallography. A plausible biosynthesis pathway has also been proposed. This compound exhibited moderate cytotoxicity (IC50 10.3–35.2 μM) against HL-60, A549, MCF-7 and SW480 human cancer cell lines.